Phase evolution, nanostructure, and oxidation resistance of polymer derived SiTiOC ceramic hybrid. Issue 5 (1st April 2019) - Anand, Rahul; Sahoo, Soumya Prakash; Nayak, Bibhuti B.; Behera, Shantanu K.
Abstract: Si based polymer-derived ceramics (PDCs) have emerged as potential materials in the fabrication of thermo-structural composites. Among the many PDCs, silicon oxycarbide (SiOC) can be fabricated from commercially available polysiloxanes and/or polysilsesquioxanes. However, SiCO based PDCs exhibit relatively limited oxidation resistance and high temperature performance compared to nitride/carbonitride counterparts. In addition, these ceramics should be compatible with carbide based substrates and oxide based top coats for thermal protection systems. Present work indicates that the incorporation of titanium into the Si-O-C system exhibits interesting properties such as crystallization, oxidation, and thermal stability. Commercially available polymethylphenylsilsesquioxane was doped with 5–20 mol% of titanium crosslinked and pyrolyzed in inert atmosphere at various temperatures. It was found that Ti ions crystallize into carbide phase at temperatures as low as 1200 °C, and that the phase separation of SiO2 shifts to temperatures beyond 1300 °C. Electron microscopy indicated the formation of nanostructured precipitates of SiC and TiC, in the size range of 4–12 nm for different conditions, with exceptional homogeneity throughout the matrix. Ab initio calculations, hypothesis based on simple bond-counting method, also confirms possible feasibilities of the doping of Ti into the SiOC structure. The SiTiOC ceramic hybrids exhibited only 17% loss on oxidation as against 41% for the SiOC ceramics. This approach indicates great promise for the application of commercial silicone polymers as high temperature resistant coatings.